Digital Media-Based Scientific Approach to Improve Learning Motivation and Content Creation Skills of Prospective Biology Teachers at Universitas Cenderawasih - Nurbaya Nurbaya; Hanida Listiani; Suriyah Satar; Maik Akobiarek; Kritiwo Martha Lemauk (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to investigate the implementation of a Scientific Approach based on digital media to improve learning motivation and digital content creation skills among prospective biology educators at Cenderawasih University. The research used a pre-experimental design with a one-group pretest-posttest model. A purposive sampling technique was used, involving 22 students of the Biology Education Study Program. The study was grounded in the challenges of 21st-century education, which requires future teachers to master both pedagogical skills and digital literacy to deliver content creatively, contextually, and effectively. The Scientific Approach was applied through stages integrated with digital media tools such as Canva, CapCut, and video editors. The findings revealed a significant improvement in students' learning motivation, supported by the Paired Sample t-Test and an N-Gain score of 0.56, indicating a moderate category. Students showed increases in value, expectancy, and affective components of motivation due to the interactive and engaging learning experience. Additionally, their ability to create digital content improved, with an average rubric score of 85.60, categorized as good. These results suggest that a Scientific Approach enriched with digital media can serve as an effective learning strategy to enhance both motivation and digital competence among future biology teachers. The model is recommended for broader adoption in teacher education institutions in response to the Merdeka Belajar initiative and the demands of the Industrial Revolution 4.0.